2012
DOI: 10.3109/15412555.2012.674164
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Improvements in Dyspnea in COPD Using a Three-Minute Constant Rate Shuttle Walking Protocol

Abstract: This 3-minute shuttle walking protocol adequately detected dyspnea and breathing pattern improvements following acute bronchodilation in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…The stepping rates were selected based on the results of Perrault et al11,15 who reported on the development and test–retest reproducibility of the 3-MST performed at stepping rates of 18, 22, 26 and 32 steps/min in patients with GOLD stage 2–4 COPD. In Perrault et al’s study, <70% of the patients were able to complete all 3 minutes of exercise at both 26 and 32 steps/min, indicating that these stepping rates are likely too intense for routine clinical use in COPD 11.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The stepping rates were selected based on the results of Perrault et al11,15 who reported on the development and test–retest reproducibility of the 3-MST performed at stepping rates of 18, 22, 26 and 32 steps/min in patients with GOLD stage 2–4 COPD. In Perrault et al’s study, <70% of the patients were able to complete all 3 minutes of exercise at both 26 and 32 steps/min, indicating that these stepping rates are likely too intense for routine clinical use in COPD 11.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lower stepping rates were used in the current study and we observed, as a result, consistently higher completion rates: 93%, 90%, 85% and 68% for 14, 16, 20 and 24 steps/min, respectively. The choice of Borg 0–10 scale to assess dyspnea was based on its wide use in COPD research and for consistency purpose with our research program on the use of the 3-minute walking and stepping tests 11,15. One interesting feature of the Borg scale is that we have a sense of how to interpret the magnitude of changes seen with treatment, a 1-point decrease in Borg dyspnea score being considered clinically relevant 24.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations